Barriers and facilitators to interprofessional simulation-based learning in a Ugandan medical school: a qualitative study - Najjuma, Josephine N.; Muhumuza, Albert; Santorino, Data; Sekyere, Samuel Owusu; Ocheke, Amaka N.; Yiltok, Simon J.; Bajunirwe, Francis (BMC Medical Education, 2024)
Background: Although Interprofessional Education (IPE) is an important component of medical education, it has only recently come under consideration in Sub-Saharan Africa. IPE occurs when two or more professions learn from, about and with each other regarding effective collaboration and the improvement of health outcomes. Current academic programs focus more on traditional approaches to training physicians, pharmacists, respiratory therapists, physiotherapists and nurses like they were independent entities. Simulation-Based Learning (SBL) is a potential platform to introduce IPE to Mbarara University of Science and Technology in southwestern Uganda that has a well- established medical simulation center but IPE has not yet been implemented. Evidence is scarce regarding the barriers and facilitators to implementing simulation-enhanced IPE (Sim-IPE). Therefore, the purpose of this study was to obtain information on barriers and facilitators of IPE from various stakeholders. Methods: We conducted a qualitative study among university administrators, faculty and undergraduate medical and nursing students. We purposively selected undergraduate students to include 3rd and 4th year nursing students and 3-5th year medical students as they had been exposed to SBL. Guided by the Consolidated Framework for Implementation Research (CFIR), we conducted semi-structured interviews with administrators and faculty members, and focus group discussions with students (n=31). The focus group discussions were uniprofessional with individuals from the same class allowing participants to share their views freely. Interviews were transcribed verbatim. We used the deductive (CFIR-driven) method to develop relevant codes and themes. Results: The barriers and facilitators identified to implementing Sim-IPE program arose from the six CFIR domains namely, the intervention characteristics, inner setting, outer setting, individual characteristics and the process. The barriers included the intervention processes such as lack of interprofessional educational resources, scheduling and communication gap between departments, the nonexistence of protected interprofessional simulation time in the curriculum, attitudes and unfavorable perceptions toward interprofessional simulation, and lack of clear assessment mechanism. The facilitators include the significance of IPE and the support of simulation-enhanced IPE (Sim-IPE). Conclusions: Implementation of Sim-IPE faces significant process and policy barriers that require addressing. There is an opportunity to capitalize on the significance that stakeholders place on IPE. The findings can be used as a benchmark for designing Sim-IPE in other low- and- middle-income countries.
Keywords: Barriers; Facilitators; Interprofessional simulation-based learning; Uganda; CFIR